2010
DOI: 10.1021/am1000745
|View full text |Cite
|
Sign up to set email alerts
|

Electrorheological Phenomena in Polyhedral Silsesquioxane Cage Structure/PDMS Systems

Abstract: It is shown, for the first time, that mixtures of sulfonated polyhedral silsesquioxane cage structures (sPOSS) and poly(dimethyl siloxane) (PDMS) with silicone oil exhibit significant electrorheological (ER) activity. At low sPOSS concentrations, less than 10 wt %, the viscosity is enhanced by approximately 100, which is comparable to the viscosity enhancements exhibited by conventional ER fluids, under the influence of comparable applied electric fields, E = 2 kV/mm. Measurements of the shear stress, sigma, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…It should also be noted that c-POSS marks the first closed cage ER structure to our knowledge with just a single functional group attached that demonstrates a strong ER effect. Previous research has already shown that octaisobutyl POSS, another closed cage structure, does not give an ER effect [9]. In addition to demonstrating the ER effect for these new ER materials, this paper seeks to answer how changing the concentration of solid cyanopropylisobutyl POSS (C 32 H 69 NO 12 Si 8 ) nanocages in a PDMS oil will affect the viscoelastic and rheological behavior of the suspension.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It should also be noted that c-POSS marks the first closed cage ER structure to our knowledge with just a single functional group attached that demonstrates a strong ER effect. Previous research has already shown that octaisobutyl POSS, another closed cage structure, does not give an ER effect [9]. In addition to demonstrating the ER effect for these new ER materials, this paper seeks to answer how changing the concentration of solid cyanopropylisobutyl POSS (C 32 H 69 NO 12 Si 8 ) nanocages in a PDMS oil will affect the viscoelastic and rheological behavior of the suspension.…”
Section: Introductionmentioning
confidence: 97%
“…Due to the highly organized base structure of POSS it is possible to add functional groups, both organic and inorganic, with precision. Furthermore it was shown that the ER effect of this class of materials is determined by the type of groups attached to the nanocage structure [9]. While the ER effect has been seen in sulfonate POSS suspensions to date no other silsesquioxane materials have been published that demonstrated similar effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advantages, ER fluids have suffered as a result of their inferior yield stress, which yields poor mechanical performance that limits their application. [11][12][13][14] The discovery of the giant ER (GER) effect has revived interest in this area. Compared with conventional ER fluids, GER fluids exhibit yield stresses that are almost an order of magnitude higher.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the versatility of these silica-based hybrid materials, their use on the development of ER fluids is very scarce. Only recently McIntyre et al published some results related to the use of hybrid materials based on functionalized polyhedral oligomeric silsesquioxane (POSS) on the development of new electrorheological fluids [35]. The authors tested two different POSS, bearing octa-isobutyl or sulfonic acid groups, and concluded that the presence of sulfonated group was responsible for the dipolar behavior and the ER response of the POSS-SO 3 H.…”
Section: Introductionmentioning
confidence: 99%